2004
DOI: 10.1007/s00424-004-1322-1
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of the ATP potentiation of hyposmotic taurine release in Swiss 3T3 fibroblasts

Abstract: Reducing osmolarity by 35% increased (3)H-taurine efflux from Swiss 3T3 fibroblasts from 0.5% to a peak of 5.7%. The presence of ATP (10-100 microM; EC(50) 1.5 microM) increased taurine efflux up to 10%, and decreased the set point for hyposmotically stimulated taurine release (HTR). ATP potentiation was mimicked by UTP, reduced by addition of suramin and pyridoxal phosphate-6-azophenyl-2',4'-disulphonic acid (PPADS) and unaffected by ADP, beta,gamma-methylene-ATP (beta,gamma-ATP) or 2-methylthio-ATP (Me-ATP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…Several groups have studied the association between extracellular ATP and volumesensitive taurine efflux and the relationship appears to be complex and dependent upon cell type: some studies have reported a stimulation of taurine release by ATP [19,30,31], some have found that ATP inhibits taurine efflux [24] whereas others have found no effect [26]. The present study shows that MDA-MB-231 and MCF-7 cells differed in their response to extracellular ATP.…”
Section: Discussionmentioning
confidence: 52%
“…Several groups have studied the association between extracellular ATP and volumesensitive taurine efflux and the relationship appears to be complex and dependent upon cell type: some studies have reported a stimulation of taurine release by ATP [19,30,31], some have found that ATP inhibits taurine efflux [24] whereas others have found no effect [26]. The present study shows that MDA-MB-231 and MCF-7 cells differed in their response to extracellular ATP.…”
Section: Discussionmentioning
confidence: 52%
“…It has become increasingly clear that agonists of these receptors, and ATP in particular, may accelerate cell-volume recovery under anisosmotic conditions and potently modulate volume-sensitive channels as well as transporters in cells, even in the absence of cell-volume changes (15,28,30,54). It has also been established that signaling linked to G protein-coupled receptors may impact cell volume, as, for example, in mouse Means Ϯ SE values (in nmol/mg of protein) from experiments performed in triplicate are shown.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of laboratories have demonstrated that stimulation of GPCRs, including several metabotropic P2Y receptors for ATP and ADP, produces limited activation of a VRAC-like pathway in non-swollen cells and greatly increases its activity in cells exposed to hypoosmotic medium (Jeremic et al 2001;Mongin and Kimelberg 2002;Mongin and Kimelberg 2003;Loveday et al 2003;Darby et al 2003;Franco et al 2004). Depending on the experimental system and the GPCR involved, PKCs have been found to play major or minor roles in the regulation of VRAC activity by GPCR agonists (Loveday et al 2003;Falktoft and Lambert 2004;Mongin and Kimelberg 2005;Heacock et al 2006;Cheema et al 2007;Ramos-Mandujano et al 2007).…”
Section: Conventional Pkc Isoforms Are Major Contributors To Vrac Regmentioning
confidence: 99%
“…An early hypothesis that cell swelling activates VRACs indirectly, via an autocrine release of ATP and subsequent activation of P2Y receptors (Wang et al 1996), was later rejected based on contradicting experimental observations in numerous cell lines (see Hazama et al 1999;Mongin and Kimelberg 2002;Mongin and Kimelberg 2003, and references therein). Nonetheless, GPCR-related signaling increases VRAC sensitivity to cell swelling and accelerates the process of cell volume regulation (Dezaki et al 2000;Mongin and Kimelberg 2002;Loveday et al 2003;Franco et al 2004), thus potentially aiding in cell volume restoration under normal and pathological conditions. VRACs are also functionally important for cell proliferation and apoptosis.…”
Section: Functional Significance For Gpcr Control Of Vrac Function Inmentioning
confidence: 99%
See 1 more Smart Citation